ESTUDO DAS SOLUÇÕES UTILIZADAS PARA LIGAÇÃO ENTRE ELEMENTOS EM SISTEMAS ESTRUTURAIS DE MADEIRA, AÇO E TUBETES DE PAPEL - Dias, Nathalia Schimidt; Salado, Gerusia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The connections must ensure a structural system capable of withstanding all the requesting efforts. They interrelate in the constructability, execution time, cost, durability and performance of the structures. Therefore, the material, format, dimensions, manufacturing (industrial or artisan), own weight, esthetics and cost of production are important. The objective of this work is to discuss the main solutions used to connect elements in structural systems of wood (wood frame), steel (light steel framing) and cardboard tubes, with some considerations on these. More than twenty types of connections and their details, used in the mentioned structural systems, were studied, being the main types, presented in this work. It can be said that for each structural system the choice of the type of connecting piece is associated with the attributes of the structural element (format, material etc) and also the needs of the project, as referring to the requested efforts.